176 Costs for Supplementing Small Ruminants Under the Various Grazing-Based Production Systems. (21st September 2022) - Karki, Uma; Shrestha, Bhuwan; Chaudhary, Santoshi; Tiwari, Anand; Karki, Lila B
Abstract: The supplementary feeding costs of small ruminants can be substantial when there is not much vegetation available for grazing or browsing. However, such costs have not been reported well and the strategies to minimize them not discussed enough. The objective of this study was to quantify the feeding costs involved in supplementing small ruminants under grazing-based production systems. Grazing studies were conducted from July to October in 2021 (88 d) in woodlands with lactating Kiko does (17) along with their young kids (33). Animals were divided into two groups (1 & 2) and randomly allocated to three woodland plots each for rotational stocking. Group 1 was allowed to rotationally graze in nearby silvopasture plots for 3-4 hours daily and Group 2 was supplemented with ad lib. hay and corn (0.5% metabolic wt.). Another study was conducted from October to December 2021 (70 d) involving 56 Kiko goats and 18 Katahdin-St. Croix ewes. During this study, there was not much foliage available, and animals were supplemented with hay (ad lib.) and corn (0.5% live wt.). Cost and amount of hay and corn used for supplementation were recorded. Data were analyzed in Excel for descriptive statistics. In the woodland study, cost for supplementing animals was $0.13 per animal per day, with 86% of the cost accounted for hay and 14% for corn. In the second study, when not much vegetation was available for grazing, cost for supplementing animals was $0.43 per animal per day, with hay cost accounting for 77% and remaining for corn. Findings of this study suggest that planted forages can be used to replace the need for purchased feed during the forage-growing period. The costs of supplementation can be significantly high during the lean period of forage production.